Polyester containers and polyester preforms
Patent Information
- Application Number
- JP2020062222
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-31
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2040-03-31
AI Technical Summary
【0017】 本発明によれば、アンチモンの内容物への溶出が問題とならない、高い衛生性を有すると共に、製造時のエネルギー消費量を低減することができるポリエステル容器を提供することができる。 また、本発明によれば、このポリエステル容器の製造に用いるポリエステルプリフォームを提供することができる。
Smart Images

Figure 0007933468000002 
Figure 0007933468000003 
Figure 0007933468000004
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a polyester container and a polyester preform used for manufacturing this polyester container. BACKGROUND ART
[0002] Polyesters such as polyethylene terephthalate (PET) are excellent in mechanical properties, chemical stability, heat resistance, gas barrier properties, transparency and the like, and are inexpensive, so they are widely used in the manufacture of containers for filling beverages and the like.
[0003] As polyesters used for manufacturing containers, those using an antimony catalyst as a polymerization catalyst (hereinafter referred to as antimony-catalyzed polyester) and those using a germanium catalyst (hereinafter referred to as germanium-catalyzed polyester) have been used. Among these polymerization catalysts, antimony-catalyzed polyesters are particularly widely used from the viewpoint of cost.
[0004] However, in recent years, it has been known that antimony may affect human health. For this reason, polyester containers using antimony-catalyzed polyester have concerns about the elution of antimony into the contents. In convenience stores and the like, containers filled with contents are placed upright, heated in hot warmers and sold, and such antimony elution becomes a particular problem in such a heated state. SUMMARY OF INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION
[0005] The present inventors manufactured polyester containers using polyesters obtained by using catalysts other than antimony, and found that such containers require more energy during production than containers obtained using antimony-catalyzed polyesters.
[0006] The present invention has been made in view of the above points, and its purpose is to provide a polyester container that has high hygiene properties, does not have the problem of antimony leaching into the contents, and can reduce energy consumption during manufacturing. Another objective of the present invention is to provide a polyester preform used in the manufacture of this polyester container. [Means for solving the problem]
[0007] The polyester container of the present invention has at least a first layer and a second layer that constitute the inner layer, The first layer is composed of a non-antimony catalyst polyester. The second layer is composed of antimony catalyst polyester.
[0008] In the polyester container of the present invention, the first layer of non-antimony catalyst polyester may be one or more polyesters selected from manganese catalyst polyester, titanium catalyst polyester, aluminum catalyst polyester, lithium catalyst polyester, and germanium catalyst polyester.
[0009] In the polyester container of the present invention, the thickness of the first layer may be 0.01 mm or more and 0.33 mm or less.
[0010] In the polyester container of the present invention, the polyester container further comprises a third layer that constitutes the outer layer, The third layer may be composed of a non-antimony catalyst polyester.
[0011] In the polyester container of the present invention, the third layer of non-antimony catalyst polyester may be one or more polyesters selected from manganese catalyst polyester, titanium catalyst polyester, aluminum catalyst polyester, lithium catalyst polyester, and germanium catalyst polyester.
[0012] In the polyester container of the present invention, the eluted antimony concentration may be less than 6 ppb.
[0013] In the polyester container of the present invention, the content of the antimony-catalyzed polyester in the polyester container may be 30 parts by mass or more and 95 parts by mass or less relative to 100 parts by mass of the total amount of resin materials contained in the polyester container.
[0014] In the polyester container of the present invention, the cross-sectional thickness of the polyester container may be 0.05 mm or more and 0.54 mm or less.
[0015] The polyester container of the present invention may be a heating container.
[0016] The polyester preform of the present invention is for producing the above polyester container. Effects of the Invention
[0017] According to the present invention, it is possible to provide a polyester container that has high sanitary properties such that elution of antimony into the contents does not pose a problem, and that can reduce energy consumption during production. Furthermore, according to the present invention, it is possible to provide a polyester preform for use in the production of this polyester container. Brief Description of the Drawings
[0018] [Figure 1] It is a schematic half-sectional view showing one embodiment of the polyester container of the present invention. [Figure 2] It is a schematic half-sectional view showing one embodiment of the polyester container of the present invention. [Figure 3] It is a schematic half-sectional view showing one embodiment of the polyester container of the present invention. [Figure 4] It is a schematic half-sectional view showing one embodiment of the polyester container of the present invention. [Figure 5] It is a schematic half-sectional view showing one embodiment of the polyester container of the present invention. [Figure 6] This is a schematic half sectional view showing one embodiment of the polyester preform of the present invention. [Figure 7] This is a schematic half sectional view showing one embodiment of the polyester preform of the present invention. [Figure 8] This is a schematic half sectional view showing one embodiment of the polyester preform of the present invention. [Figure 9] This is a schematic half sectional view showing one embodiment of the polyester preform of the present invention. [Figure 10] This is a schematic half sectional view showing one embodiment of the polyester preform of the present invention. [Mode for Carrying Out the Invention]
[0019] <Polyester Container> Figure 1 and Figure 2 are schematic half sectional views showing one embodiment of the polyester container 10 of the present invention. As shown in Figure 1 and Figure 2, the polyester container 10 of the present invention has a first layer 22 and a second layer 23, and the first layer 22 constitutes an inner layer.
[0020] Figure 3 to Figure 5 are schematic half sectional views showing one embodiment of the polyester container 10 of the present invention. In one embodiment, as shown in circle A in Figure 3 to Figure 5, the polyester container 10 of the present invention has a first layer 22, a second layer 23, and a third layer 24, where the first layer 22 constitutes an inner layer, and the third layer 24 constitutes an outer layer.
[0021] In one embodiment, as shown in Figure 1 to Figure 5, the polyester container 10 is provided with a mouth portion 11, a neck portion 12, a shoulder portion 13, a body portion 14, and a bottom portion 15.
[0022] In one embodiment, as shown in Figure 1 to Figure 5, the mouth portion 11 is provided with a threaded portion 16 onto which a cap is screwed, a tamper-evident skirt 17 below the threaded portion 16, and a support ring 18 below the tamper-evident skirt 17.
[0023] In one embodiment, the neck portion 12 is located between the support ring 18 and the shoulder portion 13, as shown in Figures 1 to 5, and has a substantially cylindrical shape with a substantially uniform diameter. In another embodiment, the shoulder portion 13 has a cylindrical shape in which the diameter gradually increases from the neck portion 12 side towards the torso portion 14 side.
[0024] In one embodiment, the body portion 14 is located between the shoulder portion 13 and the bottom portion 15, as shown in Figures 1 to 5. In another embodiment, the body portion 14 includes a panel portion 21, as shown in Figures 1 to 5. This configuration prevents deformation of the container due to changes in internal pressure when filling a polyester container with heated contents or when heating a polyester container after filling it with contents.
[0025] In one embodiment, as shown in Figures 1 to 5, the bottom portion 15 includes a recessed portion 19 located in the center and a ground contact portion 20 provided around the recessed portion 19, and is connected to the body portion 14 at this ground contact portion 20. With this configuration, deformation of the container due to increases or decreases in internal pressure can be prevented when filling the polyester container with heated contents or when heating the polyester container after filling it with contents. In one embodiment, "bottom" refers to the portion inward from the point where the polyester container touches the ground when it is standing upright.
[0026] In one embodiment, the second layer 23 is provided from the upper end of the opening 11 to the bottom 15, as shown in Figures 1 to 4. In one embodiment, the second layer 23 is provided in a part of the polyester container, for example, from the lower end of the mouth 11 to the bottom 15, as shown in Figure 5. Note that if the first layer 22 and the third layer 24 are made of the same material, as shown in Figure 5, these layers become single layers in the areas where the second layer 23 is not provided.
[0027] The polyester container 10 of the present invention may have a vapor-deposited film on the surface of the first layer 22 (not shown).
[0028] The eluted antimony concentration of the polyester container of the present invention is preferably less than 6 ppb, and more preferably less than 3 ppb. It is preferable to keep the eluted antimony concentration below 6 ppb, as this will meet the value recommended by the U.S. Food and Drug Administration (FDA) under Chapter 21 of the Common Facts (CFR). Furthermore, depending on the type of contents filled into the polyester container of the present invention, it may already contain trace amounts of antimony. By keeping the eluted antimony concentration of the polyester container below 3 ppb, the amount of antimony ultimately dissolved in the contents can be reduced. In this invention, the "antimony elution concentration of the polyester container" is measured by filling the polyester container of the present invention with ultrapure water at 23°C, leaving it upright in a 70°C environment for 14 days, and then measuring the water removed from the polyester container.
[0029] The polyester container of the present invention preferably has a capacity / weight of 5 mL / g or more and 50 mL / g or less, and more preferably 8 mL / g or more and 45 mL / g or less. By setting the capacity / weight of the polyester container to 5 mL / g or more, the blow-molding properties of the polyester container can be improved, and excessive polyester usage can be prevented, thereby reducing the amount of polyester waste and further improving the reduction of environmental impact. Furthermore, by limiting the capacity / weight of the polyester container to 50 mL / g or less, the strength of the polyester container can be improved.
[0030] The cross-sectional thickness of the polyester container of the present invention is preferably 0.05 mm or more and 0.54 mm or less, and more preferably 0.1 mm or more and 0.5 mm or less. By making the cross-sectional thickness 0.05 mm or more, the strength of the polyester container can be further improved. Furthermore, by limiting the cross-sectional thickness to 0.54 mm or less, the blow-molding properties of polyester containers can be improved. Additionally, excessive polyester usage can be prevented, thereby reducing the environmental impact. The cross-sectional thickness of a polyester container can be measured, for example, in the body of the polyester container, and refers to the point where the cross-sectional thickness is thinnest.
[0031] The polyester container of the present invention can prevent antimony and other substances from leaching into the contents, even when filled with high-temperature contents or when heated after filling. As a result, the polyester container of the present invention has high hygiene properties and can be suitably used as a container for heating.
[0032] (1st layer) In the polyester container of the present invention, the first layer constitutes the inner layer of the polyester container and is made of a non-antimony polyester. By making the first layer of a non-antimony catalyst polyester, the elution of antimony into the contents can be suppressed, resulting in a polyester container with high hygiene properties.
[0033] In this invention, "polyester" means a polymer polymerized by ester bonds. Such polyesters are usually obtained by polycondensation of a dicarboxylic acid compound and a diol compound. Examples of dicarboxylic acid compounds include malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, sebacic acid, dodecanedionic acid, eicosanedionic acid, pimelic acid, azelaic acid, methylmalonic acid and ethylmalonic acid, adamantanedicarboxylic acid, norbornenedicarboxylic acid, cyclohexanedicarboxylic acid, decalindicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 5-sodium sulfisoisophthalic acid, phenylendanedicarboxylic acid, anthracenedicarboxylic acid, phenantradiocarboxylic acid, 9,9'-bis(4-carboxyphenyl)fluorenic acid and their ester derivatives. Examples of diol compounds include ethylene glycol, 1,2-propanediol, 1,3-propanediol, butanediol, 2-methyl-1,3-propanediol, hexanediol, neopentyl glycol, cyclohexanedimethanol, cyclohexanediethanol, decahydronaphthalenedimethanol, decahydronaphthalenediethanol, norbornanediethanol, norbornanediethanol, tricyclodecanedimethanol, tricyclodecaneethanol, tetracyclododecanedimethanol, tetracyclododecanediethanol, decalindiethanol, decalindiethanol, 5-methylol-5-ethyl- Examples include 2-(1,1-dimethyl-2-hydroxyethyl)-1,3-dioxane, cyclohexanediol, bicyclohexyl-4,4'-diol, 2,2-bis(4-hydroxycyclohexylpropane), 2,2-bis(4-(2-hydroxyethoxy)cyclohexyl)propane, cyclopentanediol, 3-methyl-1,2-cyclopentadiol, 4-cyclopentene-1,3-diol, adamandiol, paraxylene glycol, bisphenol A, bisphenol S, styrene glycol, trimethylolpropane, pentaerythritol, and bis-β-hydroxyethyl terephthalate (BHET). The polyester is preferably polyethylene terephthalate, or modified polyethylene terephthalate obtained by polymerizing polyethylene terephthalate raw material monomers with copolymer monomers.
[0034] Within the limits that do not impair the properties of the present invention, the polyester may contain monomers other than dicarboxylic acid compounds and diol compounds, but the content thereof is preferably 10 mol% or less, more preferably 5 mol% or less, and even more preferably 3 mol% or less, relative to the total constituent units.
[0035] In this invention, "non-antimony catalyst polyester" means polyester obtained using a catalyst other than an antimony catalyst. In the polyester container of the present invention, the first layer of non-antimony catalyst polyester is preferably one or more polyesters selected from manganese catalyst polyester, titanium catalyst polyester, aluminum catalyst polyester, lithium catalyst polyester, and germanium catalyst polyester, and more preferably one or more polyesters selected from titanium catalyst polyester, aluminum catalyst polyester, and germanium catalyst polyester.
[0036] Examples of manganese catalysts include manganese fatty acid salts such as manganese acetate, manganese carbonate, manganese chloride, manganese acetylacetonate salts, and manganese hydroxide. Examples of titanium catalysts include titanium alkoxides such as tetra-n-propyl titanate, tetra-i-propyl titanate, tetra-n-butyl titanate, tetra-n-butyl titanate tetramer, tetra-t-butyl titanate, tetracyclohexyl titanate, tetraphenyl titanate, and tetrabenzyl titanate; titanium oxides obtained by hydrolysis of titanium alkoxides; titanium acetate; titanium oxalate; titanium oxalate; potassium titanium oxalate; sodium titanium oxalate; potassium titanate; sodium titanate; titanium titanate-aluminum hydroxide mixtures; titanium chloride; titanium chloride-aluminum chloride mixtures; titanium bromide; titanium fluoride; potassium hexafluoritate; cobalt hexafluoritate; manganese hexafluoritate; ammonium hexafluoritate; and titanium acetylacetonate. Examples of aluminum catalysts include aluminum trisacetylacetate, aluminum monoacetylacetonate bis(ethylacetoacetate), and ethylacetoacetate aluminum diisopropylate. Examples of lithium catalysts include ethyllithium, propyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, and phenyllithium. Examples of germanium catalysts include germanium dioxide, germanium tetroxide, germanium tetramethoxide, germanium tetraethoxide, germanium tetrapropoxide, germanium tetrabutoxide, germanium tetrapentoxide, and germanium tetrahexoxide.
[0037] The non-antimony catalyst polyester constituting the first layer may be virgin polyester, recycled polyester, or a mixture of virgin polyester and recycled polyester. In this invention, "recycled polyester" refers to chemically recycled polyester or mechanically recycled polyester. Chemically recycled polyester refers to polyester obtained by decomposing polyester containers down to the monomer level and then repolymerizing them. Mechanically recycled polyester refers to polyester obtained by sorting, crushing, and washing polyester containers to remove contaminants and foreign matter, obtaining flakes, and then further treating the flakes at high temperature and reduced pressure for a certain period of time to remove contaminants from inside the resin. In this invention, "virgin polyester" refers to polyester that has not undergone the above-mentioned recycling treatment, that is, unused polyester.
[0038] Within the limits that do not impair the properties of the present invention, the first layer may contain additives, such as oxygen absorbers, gas barrier resins (polyamides such as nylon 6, nylon 6,6 and polymetaxylylene adipamide (MXD6)), plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weathering agents, antistatic agents, thread friction reducers, slip agents, mold release agents, antioxidants, ion exchange agents, and coloring pigments.
[0039] In one embodiment, the first layer of the polyester container is provided in the content-filling region. In this invention, the "content-filling region" refers to the region in which the contents and the polyester container come into contact when the polyester container is filled with contents and is in an upright position. In one embodiment, the first layer is provided from a position 5 to 70 mm below the upper end of the opening to the bottom 15. Preferably, the first layer is provided from a position 5 to 15 mm below the upper end of the opening to the bottom 15. By providing the first layer from 5-70 mm below the upper edge of the opening to the bottom, the first layer can cover the content-filling area. Even when using antimony catalyst polyester in the polyester container, this prevents the antimony catalyst polyester from coming into contact with the contents, thereby further improving the hygiene of the polyester container. Furthermore, by placing the first layer from 5-70 mm below the upper edge of the opening down to the bottom, it is possible to effectively prevent cracking of the opening during automatic capping.
[0040] In one embodiment, the first layer of the polyester container is provided from a position 70 mm below the upper end of the opening to the bottom. Furthermore, it is preferable that the first layer is provided from 15 mm below the upper edge of the opening down to the bottom. This allows the first layer to cover the content-filling area, preventing the antimony catalyst polyester from coming into contact with the contents, even when antimony catalyst polyester is used in the polyester container, thereby further improving the hygiene of the polyester container. Furthermore, in the polyester container of the present invention, it is even more preferable that the first layer is provided from the upper end of the opening to the bottom. This further reduces contact between the antimony catalyst polyester and the contents, even when the container is stored on its side in a vending machine or the like, and improves the hygiene of the polyester container.
[0041] The thickness of the first layer in the polyester container is preferably 0.01 mm or more and 0.33 mm or less, more preferably 0.025 mm or more and 0.3 mm or less, and even more preferably 0.025 mm or more and 0.1 mm or less. By making the thickness of the first layer 0.01 mm or more, it is possible to effectively prevent the antimony catalyst polyester from coming into contact with the contents, even when antimony catalyst polyester is used in the polyester container. Furthermore, by making the thickness of the first layer 0.33 mm or less, the proportion of the second layer in the polyester container can be increased, and as will be described later, the energy consumption during the manufacturing of the polyester container can be further reduced. The thickness of the first layer can be measured, for example, in the body of a polyester container, and refers to the point where the first layer is thinnest.
[0042] (2nd layer) In the polyester container of the present invention, the second layer is composed of an antimony catalyst polyester. Because antimony-catalyzed polyesters have a lower melting point than polyesters obtained using other catalysts, the melting and heating temperature of the raw polyester can be lowered during the manufacture of polyester containers. This reduces the energy consumption during the manufacture of polyester containers.
[0043] Examples of antimony catalysts include antimony trioxide, antimony pentoxide, antimony acetate, triphenylantimony, and antimony glycol.
[0044] In the polyester container of the present invention, the melting point of the antimony catalyst polyester in the second layer is preferably less than 249°C, more preferably 150°C to 248°C, even more preferably 180°C to 245°C, and even more preferably 210°C to 240°C. The melting point of polyester can be measured by thermogravimetric differential thermal analysis (TG-DTA) using a DTA-60A manufactured by Shimadzu Corporation.
[0045] In the polyester container of the present invention, the difference between the melting point of the antimony catalyst polyester in the second layer and the melting point of the non-antimony catalyst polyester in the other layers is preferably 1°C or more, more preferably 5°C or more and 30°C or less, even more preferably 8°C or more and 25°C or less, and even more preferably 10°C or more and 20°C or less.
[0046] The antimony catalyst polyester constituting the second layer may be virgin polyester, recycled polyester, or a mixture of virgin polyester and recycled polyester.
[0047] In the polyester container of the present invention, the content of antimony catalyst polyester is preferably 30 parts by mass or more and 95 parts by mass or less, and more preferably 50 parts by mass or more and 80 parts by mass or less, based on 100 parts by mass of the total amount of resin material contained in the polyester container. By setting the antimony catalyst polyester content to 30 parts by mass or more per 100 parts by mass of the total amount of resin material contained in the polyester container, the energy consumption during the manufacturing of the polyester container can be further reduced. By setting the antimony catalyst polyester content to 95 parts by mass or less per 100 parts by mass of the total amount of resin material contained in the polyester container, it is possible to prevent the antimony catalyst polyester from being exposed to the first layer during the production of the polyester preform.
[0048] Within the limits that do not impair the properties of the present invention, the second layer may contain additives, such as oxygen absorbers, gas barrier resins (polyamides such as nylon 6, nylon 6,6 and polymetaxylylene adipamide (MXD6)), plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weathering agents, antistatic agents, thread friction reducers, slip agents, mold release agents, antioxidants, ion exchange agents, and coloring pigments.
[0049] The thickness of the second layer in the polyester container is preferably 0.04 mm or more and 0.49 mm or less, more preferably 0.1 mm or more and 0.4 mm or less, and even more preferably 0.1 mm or more and 0.22 mm or less. By making the thickness of the second layer 0.04 mm or more, the proportion of the second layer in the polyester container can be increased, and the energy consumption during the manufacturing of the polyester container can be further reduced. Furthermore, by setting the thickness of the second layer to 0.49 mm or less, it is possible to prevent the antimony catalyst polyester from being exposed to the contents side during the polyester preform fabrication process. The thickness of the second layer can be measured, for example, in the body of a polyester container, and refers to the point where the second layer is thinnest.
[0050] (3rd layer) In one embodiment, the polyester container of the present invention may further have a third layer. The third layer constitutes the outer layer of the polyester container and is made of the non-antimony catalyst polyester described above. By having such a configuration, the heat resistance and strength of the polyester container can be improved.
[0051] In the polyester container of the present invention, the third layer of non-antimony catalyst polyester is preferably one or more polyesters selected from manganese catalyst polyester, titanium catalyst polyester, aluminum catalyst polyester, lithium catalyst polyester, and germanium catalyst polyester, and more preferably one or more polyesters selected from titanium catalyst polyester, aluminum catalyst polyester, and germanium catalyst polyester.
[0052] Examples of manganese catalysts include manganese fatty acid salts such as manganese acetate, manganese carbonate, manganese chloride, manganese acetylacetonate salts, and manganese hydroxide. Examples of titanium catalysts include titanium alkoxides such as tetra-n-propyl titanate, tetra-i-propyl titanate, tetra-n-butyl titanate, tetra-n-butyl titanate tetramer, tetra-t-butyl titanate, tetracyclohexyl titanate, tetraphenyl titanate, and tetrabenzyl titanate; titanium oxides obtained by hydrolysis of titanium alkoxides; titanium acetate; titanium oxalate; titanium oxalate; potassium titanium oxalate; sodium titanium oxalate; potassium titanate; sodium titanate; titanium titanate-aluminum hydroxide mixtures; titanium chloride; titanium chloride-aluminum chloride mixtures; titanium bromide; titanium fluoride; potassium hexafluoritate; cobalt hexafluoritate; manganese hexafluoritate; ammonium hexafluoritate; and titanium acetylacetonate. Examples of aluminum catalysts include aluminum trisacetylacetate, aluminum monoacetylacetonate bis(ethylacetoacetate), and ethylacetoacetate aluminum diisopropylate. Examples of lithium catalysts include ethyllithium, propyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, and phenyllithium. Examples of germanium catalysts include germanium dioxide, germanium tetroxide, germanium tetramethoxide, germanium tetraethoxide, germanium tetrapropoxide, germanium tetrabutoxide, germanium tetrapentoxide, and germanium tetrahexoxide.
[0053] The non-antimony catalyst polyester constituting the third layer may be virgin polyester, recycled polyester, or a mixture of virgin polyester and recycled polyester.
[0054] Within the limits that do not impair the properties of the present invention, the third layer may contain additives, such as oxygen absorbers, gas barrier resins (polyamides such as nylon 6, nylon 6,6 and polymetaxylylene adipamide (MXD6)), plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weathering agents, antistatic agents, thread friction reducers, slip agents, mold release agents, antioxidants, ion exchange agents, and coloring pigments.
[0055] The thickness of the third layer in the polyester container is preferably 0.01 mm or more and 0.1 mm or less, and preferably 0.025 mm or more and 0.05 mm or less. By making the thickness of the third layer 0.01 mm or more, the heat resistance and strength of the polyester container can be further improved. Furthermore, by making the thickness of the third layer 0.1 mm or less, the energy consumption during the manufacturing of the polyester container can be further reduced. The thickness of the third layer can be measured, for example, in the body of a polyester container, and refers to the point where the third layer is thinnest.
[0056] (Vaporized film) The polyester container of the present invention may have a vapor-deposited film on the surface of the first layer. This can improve the gas barrier properties of the polyester container.
[0057] Examples of vapor-deposited films include those composed of metals such as aluminum, inorganic oxides such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide, organosilicon compounds such as hexamethyldisiloxane, and hard carbon films such as DLC (Diamond-Like Carbon) films. Furthermore, a hard carbon film made of DLC film is a hard carbon film also called i-carbon film or hydrogenated amorphous carbon film (aC:H), SP 3 It refers to an amorphous carbon film primarily composed of bonds.
[0058] Furthermore, the thickness of the deposited film is not particularly limited and can be, for example, between 1 nm and 150 nm.
[0059] The deposition film can be formed using conventionally known methods, such as physical vapor deposition (PVD) methods including vacuum deposition, sputtering, and ion plating, and chemical vapor deposition (CVD) methods including plasma chemical vapor deposition, thermochemical vapor deposition, and photochemical vapor deposition.
[0060] <Polyester preform> The polyester preform of the present invention is used in the manufacture of the polyester container of the present invention.
[0061] Figures 6 and 7 are schematic half-cross-sectional views showing one embodiment of the polyester preform of the present invention. In one embodiment, the polyester preform 30 of the present invention has a first layer 37 and a second layer 38, as shown in Figures 6 and 7, with the first layer 37 constituting the inner layer.
[0062] Figures 8 to 10 are schematic half-cross-sectional views showing one embodiment of the polyester preform of the present invention. In one embodiment, the polyester preform 30 of the present invention has a first layer 37, a second layer 38, and a third layer 39, as shown in Figures 8 to 10, with the first layer 37 constituting the inner layer and the third layer 39 constituting the outer layer.
[0063] In one embodiment, the polyester preform 30 of the present invention comprises a mouth portion 31, a body portion 32, and a bottom portion 33, as shown in Figures 6 to 10. In one embodiment, the mouth portion 31 corresponds to the mouth portion 11 of the polyester container 10 described above and has substantially the same shape as the mouth portion 11. Also in one embodiment, the body portion 32 corresponds to the neck portion 12, shoulder portion 13, and body portion 14 of the polyester container 10 described above and has a substantially cylindrical shape. Also in one embodiment, the bottom portion 33 corresponds to the bottom portion 15 of the polyester container 10 described above and has a substantially hemispherical shape. In one embodiment, as shown in Figures 6 to 10, the opening 31 includes a threaded portion 34 to which a cap is screwed, a hub 35 below the threaded portion 34, and a support ring 36 below the hub 35.
[0064] In one embodiment, the second layer 38 is provided from the lower end of the bottom portion 33 to the upper end of the opening portion 31, as shown in Figures 6 to 9. In one embodiment, the second layer 38 is provided as shown in Figure 10, on a portion of the polyester preform, for example, from the lower end of the bottom 33 to the lower end of the opening 31. Note that if the first layer 37 and the third layer 39 are made of the same material, as shown in Figure 10, these layers become single layers in the areas where the second layer 38 is not provided.
[0065] The cross-sectional thickness of the polyester preform of the present invention is preferably 1.3 mm to 4.7 mm, and more preferably 2.1 mm to 4.0 mm. By setting the cross-sectional thickness within the above range, the polyester container described above can be obtained. The cross-sectional thickness of the polyester preform can be measured, for example, in the torso of the polyester preform, and refers to the point where the cross-sectional thickness is thinnest.
[0066] In the polyester preform of the present invention, the content of antimony catalyst polyester is preferably 30 parts by mass or more and 95 parts by mass or less, and more preferably 50 parts by mass or more and 80 parts by mass or less, based on 100 parts by mass of the total amount of resin material contained in the polyester preform. By setting the content of antimony catalyst polyester within the above range, the polyester container described above can be obtained.
[0067] (1st layer) The material constituting the first layer in the polyester preform can be the same as the material constituting the first layer in the polyester container.
[0068] In one embodiment, as shown in Figures 7 and 9, the polyester preform 30 has a first layer 37 provided in a range of 0.4L to 0.97L from the bottom end, where L is the distance from the bottom end of the bottom portion 33 to the top end of the opening portion 31. Since the first layer 37 is provided in a range of 0.4L or more from the lower end of the bottom 33, when the polyester preform is blow-molded to form a polyester container, the first layer can cover the content-filling area. Even when using antimony catalyst polyester, this prevents the antimony catalyst polyester from coming into contact with the contents, thereby further improving the hygiene of the polyester container. Furthermore, since the first layer 37 is provided in a range of 0.97L or less from the lower end of the bottom 33, it is possible to effectively prevent cracking of the opening when the polyester preform is blow-molded to form a polyester container and capping is performed by an automated machine.
[0069] In one embodiment, the first layer may be provided from the lower end of the bottom to the upper end of the opening, or from the lower end of the bottom to the lower end of the opening.
[0070] The thickness of the first layer in the polyester preform is preferably 0.1 mm to 2.9 mm, and more preferably 0.2 mm to 2.0 mm. Furthermore, if the polyester preform includes a third layer, the thickness of the first layer in the polyester preform is preferably 0.05 mm to 1.5 mm, and more preferably 0.1 mm to 1.0 mm. By setting the thickness of the first layer in the polyester preform within the above range, the polyester container described above can be obtained. The thickness of the first layer in a polyester preform can be measured, for example, in the torso of the polyester preform, and refers to the point where the first layer is thinnest.
[0071] (2nd layer) The material constituting the second layer in the polyester preform can be the same as the material constituting the second layer in the polyester container.
[0072] The thickness of the second layer in the polyester preform is preferably 0.5 mm to 4.3 mm, and more preferably 1.9 mm to 4.0 mm. Furthermore, when the polyester preform includes a third layer, the thickness of the second layer in the polyester preform is preferably 0.4 mm to 3.7 mm, and more preferably 1.6 mm to 3.4 mm. By setting the thickness of the second layer in the polyester preform within the above range, the polyester container described above can be obtained. The thickness of the second layer in a polyester preform can be measured, for example, in the torso of the polyester preform, and refers to the point where the second layer is thinnest.
[0073] (3rd layer) The material constituting the third layer in a polyester preform can be the same as the material constituting the third layer in a polyester container.
[0074] The thickness of the third layer in the polyester preform is preferably 0.05 mm to 1.5 mm, and more preferably 0.1 mm to 1.0 mm. By setting the thickness of the third layer in the polyester preform within the above range, the polyester container described above can be obtained. The thickness of the third layer in a polyester preform can be measured, for example, in the torso of the polyester preform, and refers to the point where the third layer is thinnest.
[0075] <Method for manufacturing polyester containers> In one embodiment, the polyester container shown in Figures 1 and 2 can be manufactured by co-injecting the materials constituting the first and second layers described above to create a polyester preform, and then blow-molding this preform. The formation position of each layer can be adjusted by injection molding conditions such as resin temperature.
[0076] Furthermore, the polyester containers shown in Figure 1 and other diagrams can also be manufactured using two-color molding or insert molding. Furthermore, the polyester container shown in Figure 1, etc., can be manufactured by injection molding a non-antimony catalyst polyester into an internal mold to form a first layer, then retracting the internal mold to create a gap between the internal mold and the first layer, and finally injection molding an antimony catalyst polyester into this gap to form a second layer.
[0077] In one embodiment, the polyester container shown in Figures 3 to 5 can be manufactured by co-injecting the materials constituting the first, second, and third layers described above to produce a polyester preform, and then blow-molding this preform. When forming the second layer on a part of the preform, it is preferable to use a hot runner nozzle as disclosed in Japanese Patent Application Publication No. 2008-94454.
[0078] Furthermore, the polyester containers shown in Figure 3 and other diagrams can also be manufactured using three-color molding or insert molding. Furthermore, the polyester container shown in Figure 3, etc., can be manufactured by forming a first layer by injection molding a non-antimony catalyst polyester in an internal mold, retracting the internal mold to create a gap between the internal mold and the first layer, forming a second layer by injection molding an antimony catalyst polyester into this gap, retracting the internal mold to create gaps between the internal mold and the first and second layers, and forming a third layer by injection molding a non-antimony catalyst polyester into this gap. [Examples]
[0079] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0080] Example 1 Germanium-catalyzed polyester (germanium-catalyzed virgin PET, manufactured by Mitsui Chemicals, Inc., J-125S) and antimony-catalyzed polyester (antimony-catalyzed virgin PET, manufactured by Shinko Gosen, 5015W) were prepared. The melting points of these polyesters were measured by thermogravimetric-differential thermal analysis (TG-DTA) using a DTA-60A manufactured by Shimadzu Corporation. As a result, the melting point of the germanium-catalyzed polyester was 250°C, and the melting point of the antimony-catalyzed polyester was 240°C. A dried germanium catalyst polyester (150°C) was heated to 295°C (melting point + 45°C) and melted. Separately, a dried antimony catalyst polyester was heated to 285°C and melted. These were co-injected using an injection molding machine to produce a multilayer (two types, two layers) polyester preform, as shown in Figure 6, comprising a first layer composed of germanium catalyst polyester and a second layer composed of antimony catalyst polyester. The amount of antimony catalyst polyester used was adjusted to 80 parts by mass per 100 parts by mass of the resin material constituting the polyester preform. The polyester preform had a body thickness of 3.5 mm and a basis weight of 22 g.
[0081] Next, the polyester preform was heated to 110°C and biaxial stretch blow molding was performed in a blow molding die to obtain a multi-layer polyester container with a capacity of 500 mL, as shown in Figure 1. The mass of the polyester container in this example was 22 g. The cross-sectional thickness of the body of the polyester container was 0.32 mm.
[0082] Example 2 Aluminum catalyst polyester (aluminum catalyst virgin PET, manufactured by Indorama Polymers Public Company Ltd., RAMAPET-H3-HPC) and the above-mentioned antimony catalyst polyester were prepared. The melting point of the aluminum catalyst polyester was 249°C. Dried aluminum catalyst polyester was heated to 294°C and melted. Separately, dried antimony catalyst polyester was heated to 285°C and melted. These were co-injected using an injection molding machine to produce a multilayer (two types, two layers) polyester preform, as shown in Figure 6, comprising a first layer made of aluminum catalyst polyester and a second layer made of antimony catalyst polyester. The amount of antimony catalyst polyester used was adjusted to 80 parts by mass per 100 parts by mass of the resin material constituting the polyester preform. The polyester preform had a body thickness of 3.5 mm and a basis weight of 22 g.
[0083] Next, the polyester preform was heated to 110°C and biaxial stretch blow molding was performed in a blow molding die to obtain a multi-layer polyester container with a capacity of 500 mL, as shown in Figure 1. The mass of the polyester container in this example was 22 g. The cross-sectional thickness of the body of the polyester container was 0.32 mm.
[0084] Example 3 Titanium catalyst polyester (titanium catalyst virgin PET, manufactured by Far Eastern New Century, CB621) and the above antimony catalyst polyester were prepared. The melting point of the titanium catalyst polyester was 250°C. Dried titanium catalyst polyester was heated and melted at a temperature of 295°C. Separately, dried antimony catalyst polyester was heated and melted at a temperature of 285°C. These were co-injected using an injection molding machine to produce a multilayer (two types, two layers) polyester preform, as shown in Figure 6, comprising a first layer composed of titanium catalyst polyester and a second layer composed of antimony catalyst polyester. The amount of antimony catalyst polyester used was adjusted to 80 parts by mass per 100 parts by mass of the resin material constituting the polyester preform. The polyester preform had a body thickness of 3.5 mm and a basis weight of 22 g.
[0085] Next, the polyester preform was heated to 110°C and biaxial stretch blow molding was performed in a blow molding die to obtain a multi-layer polyester container with a capacity of 500 mL, as shown in Figure 1. The mass of the polyester container in this example was 22 g. The cross-sectional thickness of the body of the polyester container was 0.32 mm.
[0086] Example 4 The germanium catalyst polyester and the antimony catalyst polyester described above were prepared. Dried germanium catalyst polyester was heated and melted at a temperature of 295°C. Separately, dried antimony catalyst polyester was heated and melted at a temperature of 285°C. These were co-injected using an injection molding machine to produce a multilayer (2 types, 3 layers) polyester preform, as shown in Figure 8, comprising a first layer made of germanium catalyst polyester, a second layer made of antimony catalyst polyester, and a third layer made of germanium catalyst polyester. The amount of antimony catalyst polyester used was adjusted to 50 parts by mass per 100 parts by mass of the resin material constituting the polyester preform. The polyester preform had a body thickness of 3.5 mm and a basis weight of 22 g.
[0087] Next, the polyester preform was heated to 110°C and biaxial stretch blow molded in a blow molding die to obtain a multi-layer polyester container with a capacity of 500 mL, as shown in Figure 3. The mass of the polyester container in this example was 22 g. The cross-sectional thickness of the body of the polyester container was 0.32 mm.
[0088] Example 5 The above-mentioned aluminum catalyst polyester and the above-mentioned antimony catalyst polyester were prepared. Dried aluminum catalyst polyester was heated and melted at a temperature of 294°C. Separately, dried antimony catalyst polyester was heated and melted at a temperature of 285°C. These were co-injected using an injection molding machine to produce a multilayer (2 types, 3 layers) polyester preform, as shown in Figure 8, comprising a first layer made of aluminum catalyst polyester, a second layer made of antimony catalyst polyester, and a third layer made of aluminum catalyst polyester. The amount of antimony catalyst polyester used was adjusted to 50 parts by mass per 100 parts by mass of the resin material constituting the polyester preform. The polyester preform had a body thickness of 3.5 mm and a basis weight of 22 g.
[0089] Next, the polyester preform was heated to 110°C and biaxial stretch blow molded in a blow molding die to obtain a multi-layer polyester container with a capacity of 500 mL, as shown in Figure 3. The mass of the polyester container in this example was 22 g. The cross-sectional thickness of the body of the polyester container was 0.32 mm.
[0090] Example 6 The above-mentioned titanium catalyst polyester and the above-mentioned antimony catalyst polyester were prepared. Dried titanium catalyst polyester was heated and melted at a temperature of 295°C. Separately, dried antimony catalyst polyester was heated and melted at a temperature of 285°C. These were co-injected using an injection molding machine to produce a multilayer (2 types, 3 layers) polyester preform, as shown in Figure 8, comprising a first layer made of titanium catalyst polyester, a second layer made of antimony catalyst polyester, and a third layer made of titanium catalyst polyester. The amount of antimony catalyst polyester used was adjusted to 50 parts by mass per 100 parts by mass of the resin material constituting the polyester preform. The polyester preform had a body thickness of 3.5 mm and a basis weight of 22 g.
[0091] Next, the polyester preform was heated to 110°C and biaxial stretch blow molded in a blow molding die to obtain a multi-layer polyester container with a capacity of 500 mL, as shown in Figure 3. The mass of the polyester container in this example was 22 g. The cross-sectional thickness of the body of the polyester container was 0.32 mm.
[0092] Comparative Example 1 The above antimony catalyst polyester was prepared. Dried antimony catalyst polyester was heated to 285°C and melted. This was then injected using an injection molding machine to produce a single-layer polyester preform. The basis weight was 22 g. Next, the single-layer polyester preform was heated to 110°C and biaxially stretched blow-molded in a blow molding die to obtain a single-layer polyester container with a capacity of 500 mL. The mass of the polyester container in this comparative example was 22 g.
[0093] Comparative Example 2 The germanium catalyst polyester described above was prepared. Dried germanium catalyst polyester was heated to 295°C and melted. This was then injected using an injection molding machine to produce a single-layer polyester preform. The basis weight was 22g. Next, the single-layer polyester preform was heated to 110°C and biaxially stretched blow-molded in a blow molding die to obtain a single-layer polyester container with a capacity of 500 mL. The mass of the polyester container in this comparative example was 22 g.
[0094] Comparative Example 3 The above-mentioned aluminum catalyst polyester was prepared. Dry aluminum catalyst polyester was heated to 294°C and melted. This was then injected using an injection molding machine to produce a single-layer polyester preform. The basis weight was 22g. Next, the single-layer polyester preform was heated to 110°C and biaxially stretched blow-molded in a blow molding die to obtain a single-layer polyester container with a capacity of 500 mL. The mass of the polyester container in this comparative example was 22 g.
[0095] Comparative Example 4 The above titanium catalyst polyester was prepared. Dried titanium catalyst polyester was heated to 295°C and melted. This was then injected using an injection molding machine to produce a single-layer polyester preform. The basis weight was 22g. Next, the single-layer polyester preform was heated to 110°C and biaxially stretched blow-molded in a blow molding die to obtain a single-layer polyester container with a capacity of 500 mL. The mass of the polyester container in this comparative example was 22 g.
[0096] <<Evaluation of Eluted Antimony Concentration>> In the above examples and comparative examples, 480 mL of ultrapure water was filled into the containers obtained. In each container, the ultrapure water was filled from a position 28.7 mm from the top of the opening to the bottom. Next, the samples were left standing upright in a hot warmer set to 70°C for 14 days. After standing, the water was removed from the container, and its antimony concentration was measured by inductively coupled plasma mass spectrometry (ICP-MS). The measurement results are shown in Table 1.
[0097] <<Low Energy Value Assessment>> In the preparation of the containers in the above examples and comparative examples, the energy (heat) required to bring the dried raw polyester to its melting point was calculated using the following formula (I). Q x =m x ·c·ΔT (I) x: Type of catalyst Q x Energy required to bring the catalyst polyester to its melting point [J] m x : Mass of x catalyst polyester in the container [g] c: Specific heat of polyester [J / g·K] ΔT: Temperature difference between drying temperature and dissolution temperature [K] The energy was calculated assuming that the specific heat of polyester is a constant of 1.25 [J / g·K].
[0098] In Example 1, the energy required to bring the raw polyester material from its drying temperature (150°C) to its melting temperature is as follows: Q As =(22[g]×0.8)×1.25[J / g·K]×90[K]=2970.0[J] Q G =(22[g]×0.2)×1.25[J / g·K]×100[K]=797.5[J] Q total =3767.5[J] The required energy was also calculated for the containers of the other examples and comparative examples. The calculation results are shown in Table 1.
[0099] [Table 1]
[0100] As is clear from the table above, the polyester container of the present invention can effectively reduce the concentration of eluted antimony after heating, and can be suitably used as a heating container. Furthermore, it can be seen that the polyester container of the present invention can reduce energy consumption during manufacturing. [Explanation of Symbols]
[0101] 10: Polyester container 11: Mouth 12: Neck 13:Shoulder 14: Torso 15: Bottom 16: Screw part 17: Kabura 18: Support Ring 19: Sinkhole 20: Grounding part 21: Panel section 22: 1st layer 23:Second layer 24:Third layer 30: Polyester preform 31: Mouth 32: Torso 33: Bottom 34: Screw part 35: Kabura 36: Support Ring 37: 1st layer 38:Second layer 39:Third layer
Claims
1. A polyester container having at least a first layer that constitutes an inner layer and a second layer that is in contact with the first layer, The first layer is composed of a non-antimony catalyst polyester, The resin constituting the second layer is solely an antimony catalyst polyester. The aforementioned antimony catalyst polyester is antimony catalyst polyethylene terephthalate. A polyester container in which the antimony catalyst polyester is virgin polyester.
2. The polyester container according to claim 1, wherein the non-antimony catalyst polyester of the first layer is one or more polyesters selected from manganese catalyst polyester, titanium catalyst polyester, aluminum catalyst polyester, lithium catalyst polyester, and germanium catalyst polyester.
3. The polyester container according to claim 1 or 2, wherein the thickness of the first layer is 0.01 mm or more and 0.33 mm or less.
4. The aforementioned polyester container further comprises a third layer that constitutes the outer layer, The polyester container according to any one of claims 1 to 3, wherein the third layer is composed of a non-antimony catalyst polyester.
5. The polyester container according to claim 4, wherein the non-antimony catalyst polyester of the third layer is one or more polyesters selected from manganese catalyst polyester, titanium catalyst polyester, aluminum catalyst polyester, lithium catalyst polyester, and germanium catalyst polyester.
6. A polyester container according to any one of claims 1 to 5, wherein the eluted antimony concentration is less than 6 ppb.
7. The polyester container according to any one of claims 1 to 6, wherein the antimony catalyst polyester content of the polyester container is 30 parts by mass or more and 95 parts by mass or less per 100 parts by mass of the total amount of resin material contained in the polyester container.
8. The polyester container according to any one of claims 1 to 7, wherein the thickness of the cross-section of the polyester container is 0.05 mm or more and 0.54 mm or less.
9. A polyester container for heating purposes, according to any one of claims 1 to 8.
10. A polyester preform for manufacturing a polyester container according to any one of claims 1 to 9.
Citation Information
Patent Citations
Multilayer polyisophthalate and polyterephthalate product and its manufacture
JP1984067049A
Polyester resin composition and molding
JP2012077313A